Study of Thyroid Hormonal Status in Preeclamptic Patients (Medicine Today, 2014)
The physiological changes in the thyroid gland during pregnancy were well understood. Serum TSH levels were significantly increased without changes in free T3 and T4 in preeclamptic patient compared to normal pregnancy. This study tried to find out a possible relationship between preeclampsia and thyroid profile. The present study determines thyroid hormonal levels in cases of preeclampsia in the third trimester of pregnancy. TSH level were significantly higher in preeclamptic group as compared to control. A prospective case control study was conducted in the Department of Obstetrics and Gynecology, Chittagong Medical College Hospital, Chittagong. Thyroid hormone, namely Triiodothyronine (Free T3), Thyroxine (Free T4) and Thyroid Stimulating Hormone (TSH) were evaluated by radioimmunoassay. In this case control study pregnant women with preeclampsia were recruited after the diagnosis were made and compared with equal number of healthy normotensive pregnant women in third trimester. The data were analyzed using unpaired t test and chi-square test. When P value were